Interleukin-4 and interleukin-10 synergize to inhibit cell-mediated immunity in vivo. - Powrie, F; Menon, S; Coffman, R (1993)
The lack of cell-mediated (Th1-like) immunity that is often associated with strong humoral immune responses is thought to be due in part to the inhibition of Th1 effector function by the Th2-derived cytokine interleukin-10 (IL-10). This hypothesis, however, is based entirely on results from in vitro studies, wherein IL-10 has been shown to inhibit Th1 cytokine synthesis. In this study we have compared the regulatory effects of both IL-4 and IL-10 on the development of a more complex Th1 effector function in vivo, the development of delayed-type hypersensitivity (DTH) to Leishmania major in mice immune to Leishmania. The results revealed two findings unexpected from in vitro studies with Th1 clones. First, optimal inhibition of the DTH response (up to 70%), assessed by footpad swelling and leukocytic infiltration, required the combination of IL-4 and IL-10, indicating that these two activities synergized to inhibit DTH reactivity. Second, IL-4 inhibited interferon-gamma (IFN-gamma) production by lymph node cells draining the site of antigen challenge as well as did IL-10. The combination of both cytokines was no more effective than either alone. The mechanism by which IL-4 and IL-10 acted to inhibit DTH responses did not appear to be through inhibition of IFN-gamma or tumor necrosis factor production as treatment with antibodies which neutralized these activities failed to inhibit DTH responses. Inhibition of the DTH with IL-4 and IL-10 is the most effective specific regulator of DTH responses reported and the only one capable of modulating tuberculin DTH. These data establish IL-4 and IL-10 as potent inhibitors of Th1 effector function in vivo and suggest their utility in controlling deleterious Th1-mediated inflammatory responses such as occur in some infectious and autoimmune diseases.